2015
DOI: 10.1186/s12966-015-0198-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors associated with physical activity in childcare centers

Abstract: BackgroundChild care centers influence physical activity levels among children, yet little is known about the specific aspects of the environment that support generous amounts of activity. The purpose of this study was to examine the practices, and environmental aspects of the child care center that are associated with children’s moderate and vigorous physical activity.MethodsThirty-five child care centers serving 389 3 to 5 year old children were assessed for: 1) environmental characteristics of the center; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
100
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 49 publications
7
100
1
5
Order By: Relevance
“…In contrast to findings in the current study, previous studies and a systematic review have found that factors such as staff education and training, staff behaviour and encouragement, outdoor and indoor play spaces, outdoor play, the presence of vegetation, availability of portable play equipment, quality of the care environment and time outdoors, are associated with physical activity during care hours [25, 31, 4851]. Differences in reported associations between those studies and the current findings may be attributable to differences in study methodologies, operationalisation of the physical activity outcome variable, different analysis strategies, or differences in the social, cultural and political environments within which children and centers exist.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to findings in the current study, previous studies and a systematic review have found that factors such as staff education and training, staff behaviour and encouragement, outdoor and indoor play spaces, outdoor play, the presence of vegetation, availability of portable play equipment, quality of the care environment and time outdoors, are associated with physical activity during care hours [25, 31, 4851]. Differences in reported associations between those studies and the current findings may be attributable to differences in study methodologies, operationalisation of the physical activity outcome variable, different analysis strategies, or differences in the social, cultural and political environments within which children and centers exist.…”
Section: Discussioncontrasting
confidence: 99%
“…[22][23][24] Moreover, rural childcare centres have reported being influenced by additional factors associated with geographic location, such as resources and training for educators, access to facilities and space for indoor play, and access to fresh, healthy food year round. 12 The current pilot study tested the effectiveness of Healthy Start in addressing specific factors shown to influence physical activity and healthy eating within rural childcare centres.…”
Section: Discussionmentioning
confidence: 99%
“…home, childcare, community) may provide more targeted direction for intervention programming within these settings 7 . Although several studies have focused on correlates of preschool children’s physical activity and/or ST in the childcare or preschool setting, 8–11 there remains a dearth of information regarding context-specific correlates of physical activity outside of formal care.…”
Section: Introductionmentioning
confidence: 99%